Major sociological dimensions of sovereignty in a global society : global cities, enrivonmental paradigm and new quests for recognition - Čaldarović, Ognjen (2009)
U radu se prezentiraju osnovne ideje o učincima globalizacija na razvoj globalnih gradova i ističu se problemi postizanja suvereniteta država i modernih gradova.